2010
DOI: 10.1007/s00404-010-1387-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gross examination and frozen section of uterine specimen in endometrial cancer patients

Abstract: These data confirm the previous reports for the accuracy of gross examination and frozen section diagnosis in early stage and low-grade tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Poor prognostic factor in stage I endometrial adenocarcinoma consist of tumor grade, depth of myometrial invasion, lymphovascular involvement, and histological subdivision (5). Although the stage of malignancy has the main role in the prediction of the disease outcome, other factors can be indirectly affect the survival rate (12). Progression in clinical management of early stage endometrial cancers requires more predictive prognostic biomarkers to prevent 10% to 20% recurrence in such cases (2).…”
Section: Introductionmentioning
confidence: 99%
“…Poor prognostic factor in stage I endometrial adenocarcinoma consist of tumor grade, depth of myometrial invasion, lymphovascular involvement, and histological subdivision (5). Although the stage of malignancy has the main role in the prediction of the disease outcome, other factors can be indirectly affect the survival rate (12). Progression in clinical management of early stage endometrial cancers requires more predictive prognostic biomarkers to prevent 10% to 20% recurrence in such cases (2).…”
Section: Introductionmentioning
confidence: 99%
“…The main controversial issue of treatment concerns the therapeutic role of lymphadenectomy. In many centers, gynecological oncologist surgeons make a decision on whether to perform lymph‐node dissection based on macroscopic intraoperative evaluation of the degree of myometrial infiltration. A recent meta‐analysis has shown that pooled sensitivity and specificity for this approach was 75% and 95%, respectively, when using definitive histopathological diagnosis as reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…At least one year of OCP use is associated with a 50% decline in the risk of cancer; this protection is maximized by 3 years of OCP use (the effects persist for 20 -30 years) (23). The protective properties of OCPs affect 3 types of endometrial cancers, ie, endometrioid carcinoma, clear cell endometrial cancer, and papillary serous endometrial cancer (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of epithelial ovarian cancer reduces by 40% in OCP consumers, and optimal effects can be obtained by 3 years of consumption; however, the risk reduces within 3 to 6 months of OCP consumption (25). This protective effect is especially evident in nulliparous women, breast cancer (BRCA) gene I and II carriers, and those with a positive family history.…”
Section: Resultsmentioning
confidence: 99%